KELAYAKAN FINANSIAL DAN SENSITIVITAS USAHATANI KOPI ROBUSTA DI DESA KALIBARU MANIS KECAMATAN KALIBARU KABUPATEN BANYUWANGI - Kusmiati, Ati; Wati, Ninik Sumestyo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Kalibaru Manis Village is one of the villages that become Robusta coffee producers. Robusta coffee productivity in Kalibaru Manis Village is classified as low that is 1.12 Tons/Ha. Coffee produced by Kalibaru Manis Village has poor quality because the post-harvest activities that have not been following the standards Poor productivity and coffee bean quality cause the income obtained by the farmers to become low. Moreover, the income obtained by robusta coffee farmers in Kalibaru Manis Village is uncertain in each year. This uncertain income is caused by the increase of production cost and the decrease of the coffee selling price. This research aimed to find out: (1) financial feasibility of robusta coffee farming, and (2) sensitivity of robusta coffee. The area determination method used purposive method. The research methods used were descriptive method and analytic method. Sample retrieval method was done by Simple Random Sampling method. Data collection method was done by interview, observation, and documentation. Data analysis was used using financial feasibility analysis and sensitivity analysis. The research results with the interest rate level of 7% showed that : 1) Robusta coffee farming in Kalibaru Manis Village was feasible to cultivate. 2) Robusta coffee farming in Kalibaru Manis Village was not sensitive toward the changes in the production cost and robusta coffee selling price.